VD_FINDINFO HC / 2016 / 171 vom 7. März 2016 - VD Tribunal cantonal (2016)
CONTRAT DE TRAVAIL, PÉRIODE D'ESSAI, RÉSILIATION, INCAPACITÉ DE TRAVAIL, MOTIVATION DE LA DEMANDE | 335b al. 3 CO, 336c al. 2 CO